O ensino de frações inspirado na pedagogia Waldorf - Gonçalves, Natalia de Barros (2015)
Teaching fractions represents a great challenge for most teachers from the fourth grade of Elementary School until High School. To offer to the Elementary School teacher one more tool to reach students in a more satisfactory way, this work has researched and applied a more artistic way to teach the contents cited above, inspired in Waldorf Education. It was created by Rudolf Steiner right after the First World War. Besides the artistic part, it was also considered the rhythm of teaching proposed by Steiner, respecting the age of the students and calling successively to the thinking, the feelling and the will during all class activities. The work was done in a class of the sixth grade of the E.E. Prof. Adail Malmegrim Gonçalves during the year of 2013 and considered the teaching of Fractions from the very beginning.